Needs Analysis for the Development of an E-Worksheet on Global Warming Integrated with Ethno-PBL to Facilitate Students' Knowledge and Creative Thinking Skills - Wardatul Fajriyaty; Asrizal; Harman Amir; Hayyu Yumna (TIME in Physics, 2025)
The mastery of 21st-century skills, particularly the 4Cs (critical thinking, creativity, communication, and collaboration), is not yet optimally supported by conventional learning approaches. The Ethno-PBL approach is considered effective in enhancing the relevance and meaningfulness of learning by linking scientific concepts with local context and indigenous knowledge. This study employed a descriptive statistical analysis, with data collected through questionnaires administrated to teacher and student. The research revealed four main findings from the needs analysis: students' knowledge was categorized as fairly good, with an average score of 56.11, while their creative thinking skills remained low, with an average score of 30.1. The use of E-Worksheets in school learning was classified as fairly good, with a score of 41.67. The integration of ethnoscience in learning was rated as poor, with a score of 36.25. The integration of the problem-based learning (PBL) model was considered fairly good, with a score of 41.3. These results indicate that the development of an Ethno-PBL integrated E-Worksheet is urgently needed by both teachers and students to improve creative thinking skills.